2017
DOI: 10.5098/hmt.8.13
|View full text |Cite
|
Sign up to set email alerts
|

Free Convective Heat Transfer of MHD Dissipative Carreau Nanofluid Flow Over a Stretching Sheet

Abstract: Nowadays external magnetic fields are capable of setting the thermal and physical properties of magnetic-nanofluids and regulate the flow and heat transfer characteristics. The strength of the applied magnetic field affects the thermal conductivity of magnetic nanofluids and makes it aeolotropic. With this incentive, we investigate the flow and heat transfer of electrically conducting liquid film flow of Carreau nanofluid over a stretching sheet by considering the aligned magnetic field in the presence of spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…Distribution of temperature shown in Figure 7 is found to be an increasing property of E c . The results of Raju and Sandeep [58], Venkateswarlu and Satya Narayana [75], Sheikholeslami and Ganji [68], and Sandeep et al [63] corroborate with the result that temperature function grows with Eckert number due to increasing accumulation of heat energy as a result of frictional heating. For the second case,…”
Section: Non-dimensionalization and Parameterization And Methods Of S...supporting
confidence: 52%
See 1 more Smart Citation
“…Distribution of temperature shown in Figure 7 is found to be an increasing property of E c . The results of Raju and Sandeep [58], Venkateswarlu and Satya Narayana [75], Sheikholeslami and Ganji [68], and Sandeep et al [63] corroborate with the result that temperature function grows with Eckert number due to increasing accumulation of heat energy as a result of frictional heating. For the second case,…”
Section: Non-dimensionalization and Parameterization And Methods Of S...supporting
confidence: 52%
“…Distribution of temperature shown in Figure 7 is found to be an increasing property of E c . The results of Raju and Sandeep [58], Venkateswarlu and Satya Narayana [75], Sheikholeslami and Ganji [68], and Sandeep et al [63] corroborate with the result that temperature function grows with Eckert number due to increasing accumulation of heat energy as a result of frictional heating. For the second case, M = λ = n = 0.1, m = 0.2, P r = 1, Gr m = 3, α = 0.05, β 1 = 1, β 2 = 0.1, χ = 0.3, ℏ = 0.001, at various values of E c were adopted to simulate the impact of E c on the flow of air‐dust particles mixture.…”
Section: Analysis and Discussion Of Resultsmentioning
confidence: 58%
“…Tables 2 and 3 show the comparison of the results of numerical methods (NM) and that of DTM. The obtained results using DTM are in very good agreements with the Table 2 Physical parameter values of f ′′ (0) and −θ ′ (0) for Cu-Kerosene nanofluid results of the numerical method (NM) using Runge-Kutta coupled with Newton method as presented by Kumar and Kumar (2017). The high accuracy of DTM gives high confidence about validity of the method in providing solutions to the problem.…”
Section: Methods Of Solution: Differential Transform Methodssupporting
confidence: 76%
“…Extensive discussion of other applications recently studied by several researchers over stretching sheet which includes Sisko fluid flow employing Homotopy Analysis Method (HAM) Khan and Shahzad (2012), Second grade MHD fluid flow using Runge-Kutta (RK) sixth order integration scheme Das et al (2016), considered semi-infinite inclined and ideally transparent flat plate embedded in a porous medium with an Implicit finite difference scheme (IFDM), mixed convective couple stress fluid flow in a vertical channel with HAM by Kaladhar and Srinivasacharya (2014) and Prandtl-Eyring fluid flow with Keller-Box Method (KBM) Hussain et al (2017). Further a significant amount of research on Newtonian and non-Newtonian fluid flows over stretching sheet were found in (Akbar et al, 2016;Kumar et al, 2017;Chamkha et al, 2010;Reddy and Gorla, 2017).…”
Section: Introductionmentioning
confidence: 99%